Technology connects patients to tertiary care for non-COVID illnesses in pandemic times: A case study from India - Kumar, Jitender; Singh, Tarundeep; Singh, Amarjeet (Indian Journal of Community Health, 2021)
During the COVID-19 pandemic times, non-COVID patients faced many difficulties to access health care because of diversion of health resources to manage the pandemic, partial or complete closure of routine OPD services and travel restrictions due to lockdown. Increased use of technology enhanced the effectiveness of the healthcare system to maintain treatment avenues in this challenging time. Also, the pandemic accelerated diffusion of technological innovations like teleconsultation among healthcare workers and patients. The present case study is about a young, breast cancer, female patient from rural India who was diagnosed with the disease just before the pandemic times. She was put on neo-adjuvent chemotherapy in a tertiary care hospital about 150 kms away from her native place but meanwhile lockdown was imposed in India to control COVID-19 spread. She was maintained on follow up through teleconsultation services. She was facilitated through travel restrictions for chemotherapy cycles by e-pass. Her concerns regarding disease, treatment options, follow ups, effect of treatment on her fertility and adverse effects of chemotherapy during her treatment course were satisfactorily addressed through teleconsultation. Necessary investigations done nearby were sent digitally to treating doctor that minimized her visits. After completion of chemotherapy she underwent breast conservation surgery.